1983
DOI: 10.1104/pp.71.1.132
|View full text |Cite
|
Sign up to set email alerts
|

β-Galactosidases in Ripening Tomatoes

Abstract: Tomatoes (Lycopersicon escadentum L.) contained a high level of aigalactosidase activity which was due to three forms of the enzyme. During tomato ripening, the sum of their activities remained relatively constant, but the levels of the individual forms of 8-galactosidase changed markedly. The three enzymes were separated by a combination of chromatography of DEAE-Sephadex A-50 and Sephadex G-100. During ripening of tomatoes, /8-galactosidases I and III levels decreased but the P-galactosidase II level increas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
106
3
3

Year Published

1997
1997
2018
2018

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 221 publications
(114 citation statements)
references
References 14 publications
2
106
3
3
Order By: Relevance
“…These data indicate that the partially purified cotyledonary β-gal I, β-gal II and β-gal III extracted from Pitiúba cowpea were heat stable up to 50°C, and that their thermostability is similar to the β-galactosidases isolated from cotyledons of Vigna sinensis (Biswas 1987) and Vigna radiata (Kundu et al 1990), as well as from β-galactosidases isolated from other plants sources (Konno & Katoh 1986, Simos & Georgatsos 1988. However, they differ from the ones obtained with β-galactosidases isolated from radish (Sekimata et al 1989) and tomato seeds (Pressey 1983), which were inactive at 55°C or had only 50% of their initial activities at temperature ranging from 48 to 52°C, respectively.…”
Section: Resultsmentioning
confidence: 75%
See 2 more Smart Citations
“…These data indicate that the partially purified cotyledonary β-gal I, β-gal II and β-gal III extracted from Pitiúba cowpea were heat stable up to 50°C, and that their thermostability is similar to the β-galactosidases isolated from cotyledons of Vigna sinensis (Biswas 1987) and Vigna radiata (Kundu et al 1990), as well as from β-galactosidases isolated from other plants sources (Konno & Katoh 1986, Simos & Georgatsos 1988. However, they differ from the ones obtained with β-galactosidases isolated from radish (Sekimata et al 1989) and tomato seeds (Pressey 1983), which were inactive at 55°C or had only 50% of their initial activities at temperature ranging from 48 to 52°C, respectively.…”
Section: Resultsmentioning
confidence: 75%
“…These results are similar to those found for cotyledonary β-galactosidases from Vigna sinensis (Biswas 1987) and Vigna radiata (Kundu et al 1990), as well as for seeds (Agrawal & Bahl 1968, Li et al 1975, Matheson & Saini 1977 al. 1988, Sekimata et al 1989, Giannakouros et al 1991, Buckeridge & Reid 1994, shoots (Konno & Tsumuki 1993), leaves (Sawicka & Kacperska 1995) and fruits (Pressey 1983, Ogawa et al 1990, Ranwala et al 1992) of different species.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The loss of Gal can occur independently of PG activity (Carrington et al, 1993), suggesting the involvement of other classes of enzymes such as ␤-galactosidases/␤-galactanases, which have been associated with many ripening fruits (Ross et al, 1993(Ross et al, , 1994Carey et al, 1995;Lashbrook et al, 1997), and which may act on several classes of polysaccharides, including the galactan side chains of rhamnoglacturonans (Pressey, 1983). Loss of galactans has been demonstrated to accompany or even precede increased solublization of polyuronides (Gross and Wallner, 1979;Kim et al, 1991), and purified or partially purified ␤-galactosidase has been shown to catalyze an apparent decrease in the molecular size of pectins in vitro in tomato (De Veau, 1993) and melon fruits (Ranwala et al, 1992).…”
Section: Na 2 Co 3 -Soluble Fractionmentioning
confidence: 99%
“…In the combined pectic fraction (Table 111), linkages identified as typical for tomato pectic polysaccharides (based on the report of Pressey [1983] and the thorough analysis of Seymour et al 119901) comprised more than 90% of the total identified linkages. The most abundant linkages were 1,5-arabinosyl (furanosyl) residues (23% of the total), 1,4-galactosyl residues (18% of the total), and terminal galactosyl, and 1,2-and/or 1,4-xylosyl residues (not separable under the chromatographic conditions employed [15% of the total]).…”
Section: Glycosyl Linkage Composition and Labelingmentioning
confidence: 99%